2003
DOI: 10.1053/rmed.2003.1419
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to lifestyle and risk of adult onset asthma

Abstract: Obesity was associated to the risk of adult onset asthma, while short height and low leisure time physical activity can be considered as other potential risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
3
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 37 publications
5
117
3
6
Order By: Relevance
“…Our results on the BMI-derived obesity and asthma association are consistent with previous prospective studies, which found that BMI had a strong dose-response relationship with asthma development [6,17,[25][26][27][28][29][30]. In a meta-analysis study, BEUTHER and SUTHERLAND [6] analysed seven prospective studies (n5333,102) evaluating BMI and incident asthma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results on the BMI-derived obesity and asthma association are consistent with previous prospective studies, which found that BMI had a strong dose-response relationship with asthma development [6,17,[25][26][27][28][29][30]. In a meta-analysis study, BEUTHER and SUTHERLAND [6] analysed seven prospective studies (n5333,102) evaluating BMI and incident asthma.…”
Section: Discussionsupporting
confidence: 90%
“…Even though the detailed health survey allowed us to examine a large range of baseline characteristics, residual confounding from unknown characteristics may have limited our study. Dietary constituents may affect both obesity and incident asthma [28,36], and this could not be evaluated in our study. Obesity has also been suggested to increase the risk of asthma through comorbidities [32], for example, GORD and SDB are important risk factors for asthma in obese people.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of overweight and obesity on asthma hold when the analysis is done separately for women aged 15À29 and 30À49 y. These findings are consistent with other growing evidence, some from prospective cohort studies, [10][11][12][13][14][15][16][17][18][19][25][26][27][28] and provide further evidence, from a developing-country setting, that obesity may increase the risk of asthma in adult women. Underweight women have a significantly higher risk of asthma than women with a normal BMI, consistent with greater vulnerability of undernourished women in developing countries to a host of other diseases.…”
Section: Discussionsupporting
confidence: 87%
“…[42][43][44] To the extent this occurs, the estimated effect of obesity on asthma may be overestimated. However, given that several prospective cohort studies have linked obesity and weight gain to the onset of asthma both in adults 25,26 and children, 27,28 the causation is likely to be primarily from obesity to asthma. There is clearly need for prospective cohort studies of obesity and asthma in developing countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation